Bibliometric Analysis of Living Qur'an Research: A Dimensions Database Exploration (2005-2025) Using R for Statistical Computing and Bibliometrix Software - Ali, Asyiq Billah; Fi Ardillah, Maulida Fitri; Iwanebel, Fejrian Yazdajird; Taufik, Egi Tanadi (Universitas Muhammadiyah Surakarta, 2025)
This research analyses the development of living Qur'an studies between 2005 and 2025 using the keywords “Living Qur’an”, “Living Al-Qur’an”,